2002
DOI: 10.1038/sj.ejhg.5200745
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mosaicism for a MECP2 mutation associated with classic Rett syndrome in a boy

Abstract: Rett syndrome is a severe neurodevelopmental disorder that arises from mutations in the X-linked MECP2 gene. It is almost exclusively seen in girls due to the predominant occurrence of the mutations on the paternal X-chromosome, and also the early postnatal lethal effect of the disease causing mutations in hemizygous boys. We identified a boy with features of classic Rett syndrome who is mosaic for the truncating MECP2 mutation R270X. Chromosome analysis showed normal karyotype. These results indicate that a M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
63
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 18 publications
1
63
0
1
Order By: Relevance
“…On the most severe end is mosaicism for mutations presumably lethal in the non-mosaic state, as postulated for Proteus and macrocephaly-cutis marmorata telangiectatica congenita syndromes [Hamm, 1999]. Similarly, typically male lethal Xlinked disorders may be disease causing in mosaic males, as seen in classic Rett syndrome [Topcu et al, 2002]. Mosaicism for autosomal dominant disease causing mutations may cause segmental presentation of the typical findings, as in segmental neurofibromatosis type 1, a well-known entity due to the relatively high incidence and the easily identifiable skin findings.…”
Section: Discussionmentioning
confidence: 97%
“…On the most severe end is mosaicism for mutations presumably lethal in the non-mosaic state, as postulated for Proteus and macrocephaly-cutis marmorata telangiectatica congenita syndromes [Hamm, 1999]. Similarly, typically male lethal Xlinked disorders may be disease causing in mosaic males, as seen in classic Rett syndrome [Topcu et al, 2002]. Mosaicism for autosomal dominant disease causing mutations may cause segmental presentation of the typical findings, as in segmental neurofibromatosis type 1, a well-known entity due to the relatively high incidence and the easily identifiable skin findings.…”
Section: Discussionmentioning
confidence: 97%
“…in incontinentia pigmenti (IKBKG), Rett syndrome (MECP2), or chondrodysplasia punctata (EBP) (Metzenberg et al, 1999;Clayton-Smith et al, 2000;Armstrong et al, 2001;Kenwrick, 2001;Topçu et al, 2002). We assume that the paracentric inversion of the X chromosome occurred postzygotically in a particular subset of the patient's cells.…”
Section: Discussionmentioning
confidence: 99%
“…7 Males with other mosaic MECP2 mutations have been reported as well. 18,19 Since they all exhibit features of classic RTT syndrome, it is suggested that an MECP2 mutation associated with RTT syndrome in females could lead to a similar phenotype in males as a result of somatic mosaicism. The clinical diagnosis of Rett syndrome was considered previously, but it was believed at that time that this syndrome did not occur in males.…”
Section: Discussionmentioning
confidence: 99%